Prevalencia de derrame pleural como complicación de neumonía en pacientes pediátricos. Riobamba, 2019 -2020 Autor(es): - Heredia Campoverde, Cristian Gerardo (2020)
Introduction: Bacterial pneumonia in pediatric ages is one of the most frequent pathologies of hospitalization in our environment, in 2019 they constitute 24.77% of hospitalizations in the pediatric service of the HPGDR, one of the complications of this is the pleural effusion. In this study we are going to determine the prevalence of pleural effusion in pediatric ages, with the aim of analyzing the behavior of this infrequent pathology. Objective: To determine the prevalence of pleural effusion as a complication of pneumonia in patients treated at the Pediatric service of the General Provincial Hospital De Riobamba in the period from January 2019 to March 2020. Material and methods: In the review of medical records, we found that between January 2019 and March 2020, a total of 387 cases of pneumonia registered in the pediatric service, of which 7 cases complicated by pleural effusion, such This sample will be used for the study. Results: Of the 387 cases of pneumonia at pediatric ages, we observed that 1.81% of these occur with pleural effusion as a complication, being more frequent in the cold months of the year, with the greatest occurrence in infants and preschoolers. A greater number of cases in the male sex, 4 of the patients required thoracentesis as a therapeutic diagnostic method, determining Gram-positive cocci as the main causal agent and whose patients had an average of 8.2 days of hospitalization.